Histochemical Assessment of Reticulin–Collagen Patterns in the Mid-Secretory Endometrium Predicts Recurrent Pregnancy Loss - Nazerke Oshakhtiyeva; Dmitriy Klyuyev; Zhanna Amirbekova; Rinat Gatin; Anar Turmukhambetova; Kamilya Makhambetova; Irina Kadyrova; Yevgeniy Kamyshanskiy (Pathophysiology)
Background/Objectives: Normal remodeling of the extracellular matrix of the endometrium is a necessary condition for the implantation of a blastocyst. We evaluated whether the use of histochemical reticulin–collagen staining can improve the assessment of the extracellular matrix of the mid-secretory endometrium in recrudescent clinical/biochemical pregnancy losses in comparison with ultrasound and routine histological examination. Methods: We compared the histochemical pattern of reticulin–collagen endometrial biopsy (21st day of the cycle) with ultrasonography and standard histological examination of the endometrium in the following groups: (1) fertile women with gravidity ≥ 2, (gravidity = parity) and (2) women with two or more clinical/biochemical pregnancy losses. Results: A normal pattern (NP) with ordered reticulin fibers forming cellular structures was determined in 92% of biopsies with physiological reproductive status and 44% of biopsies with recrudescent reproductive failure (p < 0.05), despite the fact that there were no differences in ultrasonography and standard histological examination between the groups (p > 0.05). A histochemical pattern of insufficient secretory endometrial transformation with abnormal noodle-like pattern (aNP) collagen fibers was more common in recrudescent reproductive failure (56%) than in women with physiological reproductive status (8%) (p < 0.001), despite the fact that insufficient secretory endometrial transformation with an abnormal noodle-like pattern with collagenization (aNPC) was detected only in recrudescent reproductive failure, and it was not detected in women with physiological reproductive status (p < 0.00001). Conclusions: We determined the histochemical pattern of the extracellular matrix of the endometrium in terms of the type of reticulin–collagen, associated in our study with recrudescent clinical/biochemical pregnancy loss, with improved predictability compared to ultrasonography and standard histological examination. We propose to use the method of histochemical evaluation of the reticulin–collagen pattern in order to stratify groups of women of fertile age at risk of reproductive failure.